Operant behavior can be triggered by the position of the rat relative to objects rotating on an inaccessible platform - Pastalkova, E; Kelemen, E; Bures, J (Proceedings of the National Academy of Sciences of the United States of America, 2003)
The present study describes a task testing the ability of rats to trigger operant behavior by their relative spatial position to inaccessible rotating objects. Rats were placed in a Skinner box with a transparent front wall through which they could observe one or two adjacent objects fixed on a slowly rotating arena (d = 1 m) surrounded by an immobile black cylinder. The direction of arena rotation was alternated at a sequence of different time intervals. Rats were reinforced for the first bar-press that was emitted when a radius separating the two adjacent objects or dividing a single object into two halves (pointing radius) entered a 60 degrees sector of its circular trajectory defined with respect to the stationary Skinner box (reward sector). Well trained rats emitted 62.1 +/- 3.6% of responses in a 60 degrees sector preceding the reward sector and in the first 30 degrees of the reward sector. Response rate increased only when the pointing radius was approaching the reward sector, regardless of the time elapsed from the last reward. In the extinction session, when no reward was delivered, rats responded during the whole passage of the pointing radius through the former reward sector and spontaneously decreased responding after the pointing radius left this area. This finding suggests that rats perceived the reward sector as a continuous single region. The same results were obtained when the Skinner box with the rat was orbiting around the immobile scene. It is concluded that rats can recognize and anticipate their position relative to movable objects.
Keywords: operantní podmiňování; Behavior, Animal; chování zvířat; krysa rodu Rattus; Rats, Long-Evans; Reward; Male; potkani Long-Evans; Animals; mužské pohlaví; odměna; zvířata; Conditioning, Operant; Rats